Sustainability dalam Perspektif Islam dan Pengaruhnya terhadap Firm Value dan Firm Size melalui Profitabilitas sebagai Variabel Mediasi - Suharti, Sri; Mulyawan, Setia; Ridwan, Ahmad Hasan (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
This research is motivated by the demands of stakeholders on companies to implement sustainability. On the other hand, there is management's reluctance to implement it, because they perceive that the implementation of sustainability is not directly related to the company's main activities.The purpose of this research is to analyze the effect of corporate sustainable development (CSD) on firm value (FV) and firm size (FS) through profitability (P) as a mediating variable. This study uses a quantitative approach, and the method of correlation analysis to find the relationship between exogenous latent variables and endogenous latent variables. The data analysis technique used SEM PLS. This study found that CSD had no effect on FV and FS through profitability as a mediating variable. This is because investors tend to invest in companies that have high profitability and pay dividends. The goals of CSD can only be achieved through the transformation of education and technology by the Indonesian people which is currently in progress.